Analisis Gerakan Literasi dalam Meningkatkan Minat Baca Anak Usia Dini pada Kelompok Bermain Bustanul Wildan - N, Rina; Sari, Novita; Saputra, Desma Yuliadi (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This research was motivated by the low interest in reading of young children in Bustanul Wildan's play group, which had an impact on the low interest in reading among the students. This research aims to find out how to develop interest in reading in early childhood in Bustanul Wildan's play group through the school literacy movement. This research is a descriptive qualitative study with the aim of examining the reading interest of young children in Bustanul Wildan's play group through the school literacy movement. Data collection techniques use interviews, observation and documentation. The objects of this research are school principals, teachers and parents of students for the 2023/2024 academic year. The results of this research show that the existence of a school literacy movement activity program can increase young children's interest in reading. The school literacy movement carried out in Bustanul Wildan's play group includes Story Telling activities, raed aloud activities, reading corner activities and Wall Sticker activities. The supporting factors for these literacy movement activities are that adequate facilities play an important role for children who have a high interest in reading, starting from varied reading books, comfortable places to study, and good gadgets, plus parental assistance in guiding them effectively. Being full can make children have high enthusiasm because they feel there is more support from their parents.